ATTACHMENT ANAK TERLANTAR DENGAN PENGASUH DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK RUMAH PENGHARAPAN BARU BANDUNG BARAT - Yosua Yabes Togatorop; Dorang Luhpuri; Aep Rusmana (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Attachment is an strong emotional bond between person which is discriminative. This research aims to know the image of attachment of abandoned child with caregiver at LKSA Rumah Pengharapan Baru which included the characteristics of respondents, trust of respondent, communication of respondents and alienation of respondents. This research used descriptive analysis method with quantitative approach.The population in this research is 24 abandoned children whose age range is 10 to 18 years old and live in LKSA Rumah Pengharapan Baru Sampling technique which used in this research is census. The compiling data technique used in this research is questionnaire and documentation study. The validity of instrument is tested by Product Moment Pearson Correlation and the reliability of instrument is tested by Croncbach Alpha. The measuring instrument is using Likert Scale which provides four alternative answers namely, “Selalu”, “Sering”, “Kadang-kadang”, “Hampir Tidak Pernah” and “Tidak Pernah” in every positive and negative statements, The result of the research indicates that attachment of abandoned children with caregiver at LKSA Rumah Pengharapan Baru is in medium category. The result is known from the trust aspect in high category whose score 917, communication aspect in medium category whose score 685 and alienation in medium category whose score 507. The result indicates a problem which needs a program to increase communication an to decrease alienation aspect.